HUBUNGAN PERAN KELUARGA DENGAN PERSONAL HYGIENE PADA LANSIA DI DESA BAKALAN BOJONEGORO - Azizah, Umi; Fitriyah, Erna Tsalasatul; Anam, Muhammad Syaiful (WELL BEING, 2018)
The occurrence of aging process accompanied with various changes from both physical and psychosocial , which will cause a lack of independence of someone .This means weak seniors could no longer care for oneself , it takes the role of family , in addition the family also serves to implement health practice upbringing , namely prevent the occurrence of an impairment of health and care for family members .Based on it then the researcher interested to scrutinize the role of family relationship with personal hygiene on seniors. Research aims to understand the role of family relationships with personal hygiene in the village in in Kapas Bojonegoro district 2017 year .The research is research analytic the correlation with cross sectional approach .The population were 52 elderly , to technique sampling purposive sampling and obtained 39 elderly sample. This research result namely most of the role of family in the category of less as many as 28 ( 71,8 % ) , and cleanliness self-seniors in the category of as many as 16 less ( 41,0 % ) .Based on statistical tests analysis using rank spearman test that the results show that the value of significance in 0.04 ( it p &; 0.05 ) which means h1 accepted and there is the role of family relationship with personal hygiene at elderly in the village of Bakalan Kapas sub-district Bojonegoro district . Grew old one, they will suffered a setback especially in physical performance.It is causing the disorder in providing for his life especially cleanliness needs themselves; thereby increasing dependency need help others especially family.